2005
DOI: 10.1007/s00467-005-1977-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene locus ambiguity in posterior urethral valves/prune-belly syndrome

Abstract: Lower urinary tract obstruction by posterior urethral valves (PUV) is an important cause of congenital renal failure in male infants. Though population-based studies point to a role of genetic factors in the etiology of PUV, no clear evidence for a specific gene defect for PUV has been observed so far. Here we present a consanguineous family with four male descendants affected by PUV and a healthy girl, suggestive of autosomal recessive inheritance. One boy presented with prune-belly syndrome (PBS) in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…By contrast, several cases of posterior urethral valves have been described in siblings and monozygotic or dizygotic twins (Schreuder et al, 2008). Sex-influenced recessive inheritance has been suggested in one report (Ramasamy et al, 2005) and autosomal recessive inheritance in another (Weber et al, 2005). In reviewing these cases, it is apparent that diagnoses were often reached by ultrasound examination and based upon the appearance of the dilated bladder and prostatic urethra.…”
Section: Discussionmentioning
confidence: 80%
“…By contrast, several cases of posterior urethral valves have been described in siblings and monozygotic or dizygotic twins (Schreuder et al, 2008). Sex-influenced recessive inheritance has been suggested in one report (Ramasamy et al, 2005) and autosomal recessive inheritance in another (Weber et al, 2005). In reviewing these cases, it is apparent that diagnoses were often reached by ultrasound examination and based upon the appearance of the dilated bladder and prostatic urethra.…”
Section: Discussionmentioning
confidence: 80%
“…PUVs cause different degrees of urinary obstruction in males and even can result in end-stage renal failure. PUVs are usually isolated but can also be part of syndromes like the prune belly syndrome in association with hypoplasia of the abdominal wall and cryptorchidism [27]. There are some reports of chromosomal abnormalities, mainly involving chromosome 10 (ring chromosome and terminal q deletion) but one case with prune belly syndrome and a 6p25.3 micro deletion has also been found [28][29][30].…”
Section: Posterior Urethral Valvesmentioning
confidence: 94%
“…This supports a genetic background for PUVs. Furthermore, in one consanguineous family with four males born with PUV, a study using a DNA chip-based, genomewide linkage analysis identified two possible chromosomal loci on chromosomes 1 and 11 [27]. More families need to be identified for further studies to clarify the pathogenesis of PUVs.…”
Section: Posterior Urethral Valvesmentioning
confidence: 97%
“…Some authors even reported recurrence in 3 to 5 siblings respectively(13,14). Though several reports describe cases of monozygotic twins from whom only on boy was affected, the probability that 5 consecutive brothers were affected from PUVs were 5000-8000 5 i.e.1:3,125E+18 -3,2768E+18 if genetic had no role.…”
mentioning
confidence: 89%